Infiltration Rate of Quarternary Sediment at Rumbio Jaya, Kampar, Riau - Suryadi, Adi; Choanji, Tiggi; Wijayanti, Desy (UIR PRESS, 2018)
The study of infiltration rate was conducted at Rumbio Jaya, Kampar, Riau which closed with meandering river of Kampar. Infiltration rate data collected by using double ring infiltrometer with 30 cm and 60 cm diameter of cylinder. To support the data of infiltration test at quarternary sediment, subsurface soil profiling data were taken with hand auger drilling. The result of infiltration rate analysis shown the highest value is located at ST 2 and ST 3 (southwest part of study area) with value 248 mm/hr and 159 mm/hr. infiltration rate gradually decreasing toward northeast of study area with lowest value 2.6 mm/hr at ST 6 which caused location very closed to Kampar River. Core data from hand auger drilling support result of infiltration rate with gravelly sand layer (high porosity and permeability) are dominated at study area and some low infiltration rate location consists of thick layer of silt.